Analisis Efektivitas Zakat Profesi Dalam Program Beasiswa Pendidikan Mahasiswa (Studi Kasus Pada UPZ UINSA) - Fadilah, Chalidah Nurul; Rozikin, Muhammad Choirur; Saifulloh, Achmad Ramadhani; Yani, Sofia Indri; Sa’adah, Mazro’atus (-, 2024)
The study investigates the effectiveness of the profession in the student education scholarship program, with a focus on case studies at UPZ UINSA. A professional levy is a levy granted from the income of an individual who works or has a particular profession. The scholarship program aims to provide financial assistance to students who are financially impaired. The study uses descriptive methods with data analysis from 2021 to 2023. The results of the research showed a significant increase in the number of muzakki (people who give the zakat of the profession), number of recipients of scholarships, and number of nominal zakat professions granted. This indicates that the distribution of professional zakat funds at UPZ UINSA has undergone a positive development. However, the study also found a few challenges for UPZ UINSA in giving the employee a zakat. The conclusion of this study is that the skill of the profession is effective in the student education scholarship program, but there needs to be better efforts in overcoming the existing obstacles. This research contributes to an understanding of the role of vocational talent in improving access to education for students from poor or disadvantaged families.